2012
DOI: 10.1590/s1808-16572012000200020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de anticorpos contra a linfadenite caseosa em criações comerciais de ovinos no Distrito Federal, Brasil

Abstract: PREVALENCE OF ANTIBODIES AGAINST CASEOUS LYMPHADENITIS IN COMMERCIAL SHEEP HERDS IN THE FEDERAL DISTRICT, BRAZIL.The objective of this study was to determinate the seroprevalence of caseous lymphadenitis (CL) in commercial sheep herds in the Federal District, Brazil. One thousand and twenty-eight serum samples were collected, between March and June 2004, from all the properties (32) with at least 20 adult females in the flock. The seroprevalence of caseous lymphadenitis was determined by ELISA with secreted pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
0
0
3
Order By: Relevance
“…The seropositive properties observed in this study (55.55%) are similar to the results obtained by Carmo et al (2012) in the Federal District and by Martins et al (2010) in Bahia, who observed a seropositivity of 50% and 56%, respectively. Nevertheless, it was lower than the result obtained by , who found that seropositivity was 82.7% in Ceará and 95.9% to 100% in Minas Gerais SEYFFERT et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The seropositive properties observed in this study (55.55%) are similar to the results obtained by Carmo et al (2012) in the Federal District and by Martins et al (2010) in Bahia, who observed a seropositivity of 50% and 56%, respectively. Nevertheless, it was lower than the result obtained by , who found that seropositivity was 82.7% in Ceará and 95.9% to 100% in Minas Gerais SEYFFERT et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Estudos epidemiológicos têm demonstrado alta positividade dos animais na região nordeste (11,27), resultado que discorda do obtido no presente estudo. Este fato pode estar relacionado com a variação no sistema de manejo de cada propriedade e maior presença de plantas espinhosas na pastagem.…”
Section: Discussionunclassified
“…Levantamentos sorológicos têm sido realizados em alguns estados brasileiros, apesar de poucos trabalhos com a técnica de ELISA-indireto, estes evidenciaram elevada frequência de LC nos rebanhos. No Ceará, Carmo et al (2010) observaram frequência de 26,2% em caprinos e 84,5% das propriedades positivas para LC; no Distrito Federal, Carmo et al (2012) obtiveram prevalência de 44% em ovinos, com 50% das propriedades positivas. Seyffert et al (2010) e Guimarães et al (2009), no estado de Minas Gerais, observaram soroprevalências de 78,9% em caprinos e 75,8% em ovinos, com 98% e 95,9% dos rebanhos apresentando pelo menos um animal soropositivo para LC, respectivamente.…”
Section: Introductionunclassified
“…A importância da LC no Brasil pode ser estimada pelo aumento da participação dos pequenos ruminantes na pecuária nacional e sua relação com o impacto econômico desta doença (Guimarães et al 2009, Seyffert et al 2010, Carmo et al 2012, Faccioli-Martins et al 2014. Embora a LC tenha sido detectada como problema endêmico na mais importante área de produção de caprinos do país, o Nordeste brasileiro (Brown et al 1987), uma análise abrangente e mais recente desta prevalência nos rebanhos caprinos brasileiros se faz necessária.…”
Section: Introductionunclassified